Understanding and defining bullying – adolescents’ own views - Hellström, Lisa (Arch Public Health, 2015)
BACKGROUND: The negative consequences of peer-victimization on children and adolescents are major public health concerns which have been subjected to extensive research. Given all efforts made to analyze and estimate the social and health consequences of peer-victimization, the adolescents’ own experiences and understandings have had surprisingly little impact on the definition of bullying. Therefore, the aim of the current study is to explore adolescents’ definitions of bullying. METHODS: A questionnaire study (n = 128) and four focus group interviews (n = 21) were conducted among students aged 13 and 15. First, gender and age differences were analyzed with respect to what behaviors are considered bullying (questionnaire data). Second, analysis of what bullying is (focus group interviews) was conducted using qualitative content analysis. RESULTS: The adolescents own understanding and definition of bullying didn’t just include the traditional criteria of repetition and power imbalance, but also a criterion based on the health consequences of bullying. The results showed that a single but hurtful or harmful incident also could be considered bullying irrespective of whether the traditional criteria were fulfilled or not. Further, girls and older students had a more inclusive view of bullying and reported more types of behaviors as bullying compared to boys and younger students. CONCLUSIONS: The results of the current study adds to the existing literature by showing that adolescents consider the victim’s experience of hurt and harm as a criterion for defining bullying and not only as consequences of bullying. This may be of special relevance for the identification and classification of bullying incidents on the internet where devastating consequences have been reported from single incidents and the use of the traditional criteria of intent, repetition and power imbalance may not be as relevant as for traditional bullying. It implies that the traditional criteria included in most definitions of bullying may not fully reflect adolescents’ understanding and definition of bullying. Assessments of bullying behaviors that ask adolescents to strictly adhere to the traditional definition of bullying might not identify all adolescents experiencing peer victimization and therefore not provide estimates of prevalence rates reflecting adolescents’ own understanding of bullying.